Diversity in Addressing Reaction Mechanisms of Nano‐Thermite Composites with a Layer by Layer Structure. Issue 3 (15th November 2017) - Sui, Hongtao; LeSergent, Lauren; Wen, John Z.
Abstract : The reaction mechanisms and microstructures of various layered nano‐thermite composites are investigated through characterization of their energetic properties. Migration of reactive components across the reaction zone is analyzed, which plays an important role in determining the process initiation, reaction propagation, and chemical stability at low temperatures. Distinct types of nanoparticles are deposited onto filter paper in a sequence, using the vacuum filtration method, which promotes intimate contact between neighboring reactive layers. Scanning Electron Microscopy (SEM) images demonstrate a well‐defined contact region between the two layers in the Al/CuO or Al/NiO composites. Differential Scanning Calorimetry (DSC) data shows that the thermite reaction occurs below the melting temperature of Al, resulting in rapid heat release, and improves reaction initiation. Elemental mapping results reveal the migration of Al, Ni/Cu, and oxygen before and after the thermite reaction, which is arranged during thermogravimetric analysis (TGA). This analysis indicates the dominant pathway of the thermite reaction in each composite, through either decomposition of the CuO nanoparticles in the Al/CuO composite or through direct migration of reactive components across the conducting surface within the Al/NiO composite. Abstract : Layer‐by‐layer structured Al–CuO and Al–NiO nanoparticles are investigated via characterization of their microstructures and elemental mapping. Experimental data indicates for Al–CuO the reaction involves decomposition of CuO into oxygen, while for Al–NiO migration of reactive species across the conducting surface is critical.